HR Development Through Capacity Building To Increase Company Productivity - Adhi Susano; Heru Subiantoro; Meirinaldi Meirinaldi (CV. Publikasi Indonesia, 2023)
In the era of globalization, human resources (HR) is an important asset for every company to gain competitive advantage. For the organization to continue to exist on a national and international scale, human resource development (PSDM) is a decisive factor in achieving goals and objectives. The research is included in the type of qualitative research, namely research with descriptive methods. This study intends to provide an in-depth description related to the research object, namely the development of human resource capacity (HR). To achieve the company's performance and goals, it is very important to implement an HR capacity-building program on an ongoing basis. Organizational human resource development has a direct impact on talent development, employee resilience, and career development. It also offers companies a new paradigm to develop their human capital. The fundamental components that determine the existence of an organization in a cruel corporate environment include aspects of competence, talent, and resilience. Companies that implement competence must pay attention to management levels and HRM stages. Potential employees who perform well under pressure contribute to organizational consistency and competition. By considering the two strategic options of matching people to roles and matching roles to people, talent-based HRM needs to be contextualized. produce workers who have the knowledge, skills, money, affluence, talents, attitudes, and dispositions necessary to inspire others. It is important to create AQ-based human resources who can deal with any problem, act responsibly, set boundaries for problems, and refuse to give up quickly. With the aspect of resilience, employees can calm their intentions, smother, and catch problems to take advantage for the sake of organizational effectiveness to achieve success and exist in a competitive world.